2019
DOI: 10.1111/cmi.13135
|View full text |Cite
|
Sign up to set email alerts
|

Edwardsiella ictaluri evpP is required for colonisation of channel catfish ovary cells and necrosis in anterior kidney macrophages

Abstract: Edwardsiella ictaluri is a Gram-negative facultative anaerobe that can survive inside channel catfish phagocytes. E. ictaluri can orchestrate Type VI Secretion System (T6SS) for survival in catfish macrophages. evpP encodes one of the T6SS translocated effector proteins. However, the role of evpP in E. ictaluri is still unexplored. In this work, we constructed an E. ictaluri evpP mutant (EiΔevpP) and assessed its survival under complement and oxidative stress. Persistence of EiΔevpP in catfish as well as attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
0
11
1
Order By: Relevance
“…Nevertheless, in present study, it is noteworthy that more early apoptosis could be observed than late apoptosis in E. piscicida-infected macrophages, implying that cell death by apoptosis might play a significant role in E. piscicida-macrophage interactions. Although EvpP have been demonstrated to exert inhibitory effect on apoptosis and pyroptosis in E. piscicida-infected macrophages, for E. ictalurid, EvpP were shown to increase apoptosis and necrosis in anterior kidney macrophages (Kalindamar et al, 2019). Additionally, in contrast to E. piscicida, deletion of evpP were not found to affect the virulence of E. ictalurid significantly in that study.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Nevertheless, in present study, it is noteworthy that more early apoptosis could be observed than late apoptosis in E. piscicida-infected macrophages, implying that cell death by apoptosis might play a significant role in E. piscicida-macrophage interactions. Although EvpP have been demonstrated to exert inhibitory effect on apoptosis and pyroptosis in E. piscicida-infected macrophages, for E. ictalurid, EvpP were shown to increase apoptosis and necrosis in anterior kidney macrophages (Kalindamar et al, 2019). Additionally, in contrast to E. piscicida, deletion of evpP were not found to affect the virulence of E. ictalurid significantly in that study.…”
Section: Discussioncontrasting
confidence: 60%
“…A recent study revealed the role of EvpP in promoting the pathogenesis of E. piscicida via inhibiting the phosphorylation of Jnk signaling, subsequently suppressing the caspy-inflammasome signaling cascades, contributing to the inhibition of neutrophils recruitment (Tan et al, 2019). In E. ictalurid, EvpP were demonstrated to be required for colonization of catfish ovary cell and increase apoptosis and necrosis in anterior kidney macrophages (Kalindamar et al, 2019). These reports increasingly reveal the importance of EvpP in E. piscicida-infection.…”
Section: Introductionmentioning
confidence: 98%
“…T6SS effectors are involved in bacterial survival in oxidative stress ( 54 , 55 ). In E. ictaluri and E. piscicida , the T6SS effector EvpP enhanced resistance to oxidative stress ( 56 , 57 ). To investigate the role of Hcp family proteins of T6SS in E. ictaluri stress resistance, we applied nitrosative and oxidative stress with SNP and H 2 O 2 in BHI and in MM19-P to imitate stressful phagosome conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Promotes adhesion and internalization. Kalindamar et al, 2020 (Continued) Three T6SS effectors with putative anti-eukaryotic activities were identified by analyzing the Vpr secretome. Vpr01570 contains an N-terminal MIX V domain and a C-terminal CNF1 (cytotoxic necrotizing factor 1) deamidase domain that targets and activates Rho GTPases.…”
Section: E Tarda Evppmentioning
confidence: 99%
“…EvpP toxin is involved in adhesion and internalization of E. ictaluri in catfish ovary cells. EvpP plays a role in growth regulation in the phagolysosome where oxidative stress and limited nutrients are present, and also favors survival and increases apoptosis and necrosis in catfish anterior kidney macrophages (Kalindamar et al, 2020).…”
Section: Edwardsiellamentioning
confidence: 99%